Teaching in hunter–gatherer infancy - Barry S. Hewlett; Casey J. Roulette (Royal Society Open Science, 2016)
A debate exists as to whether teaching is part of human nature and central to understanding culture or whether it is a recent invention of Western, Educated, Industrial, Rich, Democratic cultures. Some social–cultural anthropologists and cultural psychologists indicate teaching is rare in small-scale cultures while cognitive psychologists and evolutionary biologists indicate it is universal and key to understanding human culture. This study addresses the following questions: Does teaching of infants exist in hunter–gatherers? If teaching occurs in infancy, what skills or knowledge is transmitted by this process, how often does it occur and who is teaching? The study focuses on late infancy because cognitive psychologists indicate that one form of teaching, called natural pedagogy, emerges at this age. Videotapes of Aka hunter–gatherer infants were used to evaluate whether or not teaching exists among Aka hunter–gatherers of central Africa. The study finds evidence of multiple forms of teaching, including natural pedagogy, that are used to enhance learning of a variety of skills and knowledge.